Relevance of Local Wisdom towards Efforts to Achieve Sustainable Food Sovereignty in Bangsal Village, Pampangan District, Ogan Komering Ilir Regency - Eka Mulyana; Yulian Junaidi; Madina Soraya (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2021)
This study aims paused analyzing the relevance of local wisdom toward efforts in achieving sustainable food sovereignty in Bangsal Village, Pampangan District, Ogan Komering Ilir Regency. This exploratory descriptive study was conducted in Bangsal Village, Pampangan District, Ogan Komering Ilir Regency in February 2020. Data collected were both of primary and secondary data. The analyses show that the swamp marshland was managed into three parts, i.e. buffalo husbandry, swamp fish farming and rice farming is provably more appropriate. For the buffalo husbandry, the community apply their local wisdom of kalang (shepherd) system. While for the fish farming, the capture fishery (beje) system was used. Futhermore, for rice cultivation, it consists of several stages with their respective local wisdom used, i.e. a) tillage, using rewang and perarian systems, b) Seeding, using seeds from their last harvest, c) planting, transplanting, spaced planting, or direct planting (tunjam) d) fertilizing, using weeds or wild plants, e) maintaining, with local wisdom, using scarecrow and plastic surrounding field, f) harvest, mutual cooperation in cutting the rice with sickle (ngarit bersama), and g) post-harvest, selling the harvest directly or self-storage. The results show mean of 54.60 from the 7 indicators and it was included in high criteria. It is conluded that there was a significant relevance between local wisdom and efforts to achieve sustainable food sovereignty in Bangsal Village.